Experimental study of gas adsorption using high-performance activated carbon: Propane adsorption isotherm - Tine Aprianti; Harrini Mutiara Hapsari; Debby Yulinar Permata; Selvia Aprilyanti; Justin Sobey; Kallan Pham; Srinivasan Kandadai; Hui Tong Chua (Universitas Negeri Padang, 2024)
Activated carbon is widely used for its diverse adsorptive abilities, with a vast range of current and emerging uses. This study developed a data set for high-performing activated carbon, its adsorption abilities with differing adsorbents, and an understanding of what deviations are present compared to the widely used adsorption models. This study included the construction of Tóth isotherms in varying conditions. Building a strong isotherm correlation is desired, with an understanding of the relationship between the pores of the activated carbon sample, operating parameters, and the adsorbent. The present data could complement efforts in designing adsorbed natural gas storage systems. Experimental data was collected using a Constant Volume Variable Pressure (CVVP) apparatus, consisting of a temperature-regulated vessel containing the activated carbon sample dosed with varying adsorbents through a controlled dosing vessel. Analysis of the derived data gave a well-fitted Tóth adsorption isotherm, giving the maximum specific adsorption capacity of the activated carbon to be 2.28 g of propane per gram of activated carbon with a standard error of regression